Physicochemical characterization of fruit fillings for bakery products (@limentech, Ciencia y Tecnología Alimentaria, 2023)
Fruit fillings are an understudied product. Their design and formulation must take into account a series of factors inherent to their applications, including stability during thermal treatments such as baking and freezing, during which their quality must remain intact. Throughout this study, a physicochemical characterization was carried out on different baking fruit fillings prepared by a Caucana company, including Guava Fillings FRG1, FRG2, and FRG3 (different formulations), Blackberry Filling (RCZ), and Chocolate Filling (RCCH) using standard methodology. The physicochemical characterization of the fillings revealed data on their moisture content, pH, soluble solids, total solids, ether extract, and ash content. Among the results collected during this analysis, the soluble solids and pH contents found for the FRG1, FRG2, FRG3, and RCZ samples are highlighted, as these values can be compared with the supplier's requirements(FAMESA 404,FAMESA 425), with values from 74.8% to 79.6% for soluble solids and for pH from 3,84 to 4,22. It was determined that the pH of the FRG1, FRG2, and FRG3 fillings is above the established range according to the FAMESA Technical Sheet, as are the soluble solids contents, which are below the expected range. As for the Blackberry Filling, it meets the desired ranges according to the Technical Sheet for both soluble solids and pH.
Keywords: Bakeable Fruit fillings; Blackberry; Guava; Chocolate; Physicochemical characterization